2021
DOI: 10.3389/fcimb.2021.633242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking on Inflammatory Markers in a Healthy Population as Analyzed via the Gut Microbiota

Abstract: The number of people who smoke has increased in recent years, and the incidence of smoking-related diseases increases annually. This study was conducted to explore whether smoking affects diseases via changes in the gut microbiota. We enrolled 33 smokers and 121 non-smokers. We collected fecal samples from all participants and performed whole-genome sequencing. Smoking significantly affected the gut microbiota. At the phylum through genus levels, the smokers’ microbiotas showed slight changes compared with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 57 publications
(59 reference statements)
4
38
0
Order By: Relevance
“…At the OTU level, a previous study conducted in a healthy population suggested that the smoking-related microbiota composition profile features the increased R. bromii and depleted A. muciniphila and B. nordii, which is in line with our study in CAD smokers (15). We found via intergroup comparison that the OTUs enriched in current smokers comprise several opportunistic pathogens such as H. parainfluenzae and Klebsiella sp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…At the OTU level, a previous study conducted in a healthy population suggested that the smoking-related microbiota composition profile features the increased R. bromii and depleted A. muciniphila and B. nordii, which is in line with our study in CAD smokers (15). We found via intergroup comparison that the OTUs enriched in current smokers comprise several opportunistic pathogens such as H. parainfluenzae and Klebsiella sp.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that Desulfovibrio DNA progressively increased with the smoking burden (pack-years) (26). The overall decreased Veillonella abundance in smokers at the genus level is in line with an earlier study (15). Manhattan plots showed the contributions of differentially abundant OTUs at the class level (Figure 1C).…”
Section: Gut Microbiome Composition In Male Patients With Cad Varies With Different Smoking Statussupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, smoking cessation induces only a minor change in microbiota after 12 weeks in ex-smokers, while other research shows a shift after 9 weeks with an increase of Firmicutes and Actinobacteria and a decrease in Bacteroidetes and Proteobacteria [245]. The reduction of anti-inflammatory bacteria such as F. prausnitzii and Akkermansia muciniphila with a higher abundance of pro-inflammatory bacteria such as Ruminococcus gnavus and Bacteroides vulgatus, as revealed by a metagenomic sequencing, can explain the systemic pro-inflammatory action of smoke [246].…”
Section: Cigarette Smokingmentioning
confidence: 95%
“…LPS is a protein present on the outer surface of gram-negative bacteria. Generally, its target is TLR-4, which delivers the action on different receptors [15]- [17]. Human immune cells recognize extracellular LPS through the Tolllike receptor-4 (TLR-4).…”
Section: Introductionmentioning
confidence: 99%